Mutations in KARS, encoding lysyl-tRNA synthetase, cause autosomal-recessive nonsyndromic hearing impairment DFNB89. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Azeem, Zahid; Antonellis, Patrick J; Pollock, Lana M; Khan, Saadullah; Andrade-Elizondo, Paula B; Chiu, Ilene; Adams, Mark D; Basit, Sulman; Smith, Joshua D; Nickerson, Deborah A; et al. (Am J Hum Genet, 2013)
Previously, DFNB89, a locus associated with autosomal-recessive nonsyndromic hearing impairment (ARNSHI), was mapped to chromosomal region 16q21-q23.2 in three unrelated, consanguineous Pakistani families. Through whole-exome sequencing of a hearing-impaired individual from each family, missense mutations were identified at highly conserved residues of lysyl-tRNA synthetase (KARS): the c.1129G>A (p.Asp377Asn) variant was found in one family, and the c.517T>C (p.Tyr173His) variant was found in the other two families. Both variants were predicted to be damaging by multiple bioinformatics tools. The two variants both segregated with the nonsyndromic-hearing-impairment phenotype within the three families, and neither mutation was identified in ethnically matched controls or within variant databases. Individuals homozygous for KARS mutations had symmetric, severe hearing impairment across all frequencies but did not show evidence of auditory or limb neuropathy. It has been demonstrated that KARS is expressed in hair cells of zebrafish, chickens, and mice. Moreover, KARS has strong localization to the spiral ligament region of the cochlea, as well as to Deiters' cells, the sulcus epithelium, the basilar membrane, and the surface of the spiral limbus. It is hypothesized that KARS variants affect aminoacylation in inner-ear cells by interfering with binding activity to tRNA or p38 and with tetramer formation. The identification of rare KARS variants in ARNSHI-affected families defines a gene that is associated with ARNSHI.
Keywords: Animals; Case-Control Studies; Chickens; Cochlea; Computational Biology; Consanguinity; Female; Genetic Linkage; Hair Cells, Auditory, Inner; Haplotypes; Hearing Loss; Homozygote; Humans; Lysine-tRNA Ligase; Male; Mice; Mutation, Missense; Pedigree; Transfer RNA Aminoacylation; Zebrafish